2016
DOI: 10.1038/nmicrobiol.2016.33
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the sexual origin of heterokaryosis in arbuscular mycorrhizal fungi

Abstract: Sexual reproduction is ubiquitous among eukaryotes, and fully asexual lineages are extremely rare. Prominent among ancient asexual lineages are the arbuscular mycorrhizal fungi (AMF), a group of plant symbionts with a multinucleate cytoplasm. Genomic divergence among co-existing nuclei was proposed to drive the evolutionary success of AMF in the absence of sex(1), but this hypothesis has been contradicted by recent genome analyses that failed to find significant genetic diversity within an AMF isolate(2,3). He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
301
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(324 citation statements)
references
References 65 publications
18
301
5
Order By: Relevance
“…Previous studies have proposed that the heterokaryosity in AMF species drives variable genetic combinations of mycelia 68 . Recent genomic studies, furthermore, discovered signatures of sexual reproduction within the dikaryon-like stage 16,69 . Our hypothesis does not exclude current theories for the genetic and phenotypic plasticity of AMF species (heterokaryosis and sexual reproduction) but proposes a multilayered diversification mechanism leading to their widespread distribution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have proposed that the heterokaryosity in AMF species drives variable genetic combinations of mycelia 68 . Recent genomic studies, furthermore, discovered signatures of sexual reproduction within the dikaryon-like stage 16,69 . Our hypothesis does not exclude current theories for the genetic and phenotypic plasticity of AMF species (heterokaryosis and sexual reproduction) but proposes a multilayered diversification mechanism leading to their widespread distribution.…”
Section: Resultsmentioning
confidence: 99%
“…Genomic data have been provided for Rhizophagus irregularis DAOM-181602 (=DOAM-197198) 12–14 , Gigaspora rosea 12 , Rhizophagus clarus 15 , and other isolates of R. irregularis 14,16 . These studies revealed potential host-dependent biological pathways 12,17 and candidate genes for plant infection and sexual reproduction 15,16,17 . However, fragmented genome sequences limit the ability to analyze repetitive structures and to distinguish between orthologous and paralogous genes 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Sexual reproduction is unknown but supported by genome evidence (Ropars et al 2016). Asexually formed chlamydospore-like spores are borne terminally, laterally, or intercalary on specialized hyphae.…”
Section: Taxonomymentioning
confidence: 99%
“…(Halary et al, 2011), suggesting that sexual reproduction in AMF could be possible. A putative multi-allelic mating-type locus, containing genes with structural and evolutionary similarity with mating-type loci of other taxa, was found in the genomes of five isolates of R. irregulare (Ropars et al, 2016). Additional studies should be carried out in order to investigate whether anastomosis between different AMF genotypes may prelude parasexual cycle or sexual recombination, and thus affect their reproductive success.…”
Section: Asymbiotic Myceliummentioning
confidence: 99%